2021
DOI: 10.1021/acs.accounts.0c00840
|View full text |Cite
|
Sign up to set email alerts
|

Total Synthesis of Stelletins through an Unconventional Annulation Strategy

Abstract: Conspectus Marine ecosystems present the largest source of biodiversity on the planet and an immense reservoir of novel chemical entities. Sessile marine organisms such as sponges produce a wide range of complex secondary metabolites, many of these with potent biological activity engineered for chemical defense. That such compounds exert dynamic effects outside of their native context is perhaps not surprising, and the realm of marine natural products has attracted considerable attention as a largely untapped … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 58 publications
0
11
0
Order By: Relevance
“…Natural Product Reports through cyclizations of 2,3-oxidosqualene (69) via chair−boat−chair (191) transition states (Scheme 8). 57,63,64 Similarly, it has been suggested that the biosynthesis of the basic core skeleton of malabaricane triterpenoids also proceeds through cyclizations of 2,3-oxidosqualene (69) via a chair-chair-chair (193) transition state 57,63,64 and triterpene synthases are responsible to generate the malabaricane basic skeleton 196 (Scheme 8). 64,65 It has been reported that two Arabidopsis thaliana genes including At5g4810 and At4g15340 encode OSCs which furnish arabidiol and thalianol.…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Natural Product Reports through cyclizations of 2,3-oxidosqualene (69) via chair−boat−chair (191) transition states (Scheme 8). 57,63,64 Similarly, it has been suggested that the biosynthesis of the basic core skeleton of malabaricane triterpenoids also proceeds through cyclizations of 2,3-oxidosqualene (69) via a chair-chair-chair (193) transition state 57,63,64 and triterpene synthases are responsible to generate the malabaricane basic skeleton 196 (Scheme 8). 64,65 It has been reported that two Arabidopsis thaliana genes including At5g4810 and At4g15340 encode OSCs which furnish arabidiol and thalianol.…”
Section: Reviewmentioning
confidence: 99%
“…57,63,64 Similarly, it has been suggested that the biosynthesis of the basic core skeleton of malabaricane triterpenoids also proceeds through cyclizations of 2,3-oxidosqualene (69) via a chair-chair-chair (193) transition state 57,63,64 and triterpene synthases are responsible to generate the malabaricane basic skeleton 196 (Scheme 8). 64,65 It has been reported that two Arabidopsis thaliana genes including At5g4810 and At4g15340 encode OSCs which furnish arabidiol and thalianol. 8,66,67 In addition, numerous malabaricanes have been obtained via site-directed mutagenesis of A. acidocaldarius squalene hopene cyclase which in turn comprise point mutants of Tyr420, Phe601 and Ile261.…”
Section: Biosynthesis Of Isomalabaricane and Malabaricane Trietrpenoidsmentioning
confidence: 99%
“…Notably, previous structure‐activity relationship studies have shown that stellettin A (STELA), stellettin B (STELB), and STELE share a singular trans‐syn‐trans perhydrobenz[e]indene core that is indispensable for their anticancer effects. [ 9 ] Therefore, the stellettin compounds represent attractive anticancer drug candidates for in‐depth investigation.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7] Of these, rhabdastrellic acid A, stelletin A, and stelletin E have been accomplished through total syntheses, providing materials for studying biological mechanisms. 8,9 To date, over 70 isomalabaricane analogs have been isolated from R. globostellata. 6,7,[10][11][12][13][14][15][16][17][18] It has been shown that chemical structures of isomalabaricanes mostly differ at the side chain by the oxidative degeneration, cyclization, and isomerization of double bonds.…”
Section: Introductionmentioning
confidence: 99%